2021
DOI: 10.30935/scimath/11206
|View full text |Cite
|
Sign up to set email alerts
|

Pre-service Middle School Mathematics Teachers’ (Mis)conceptions of Definitions, Classifications, and Inclusion Relations of Quadrilaterals

Abstract: The purpose of this study is to examine pre-service middle school mathematics teachers' (mis)conceptions related to definitions, classifications, and inclusion relations of convex quadrilaterals through a case study research design. The participants of the study were 20 pre-service middle school mathematics teachers who attended a must course, "The Methods of Teaching Mathematics" in a public university in Ankara, Turkey. Purposive sampling strategy was used to select the participants. The data were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 18 publications
4
5
0
Order By: Relevance
“…Stephen, almost all the participants' attempts to define the shapes, made no effort to consider the inclusion relation among the quadrilaterals. This finding supports that of Baktemur et al (2021), who also found, in their study, that the participating teachers described the types of quadrilaterals without any attention to the inclusion criteria among the shapes.…”
supporting
confidence: 88%
See 4 more Smart Citations
“…Stephen, almost all the participants' attempts to define the shapes, made no effort to consider the inclusion relation among the quadrilaterals. This finding supports that of Baktemur et al (2021), who also found, in their study, that the participating teachers described the types of quadrilaterals without any attention to the inclusion criteria among the shapes.…”
supporting
confidence: 88%
“…Literature shows similar findings as reported by Ulger and Broutin (2017). Baktemur et al (2021) investigated pre-service teachers' conceptions and misconceptions of definition, classification and inclusion in which 20 purposely selected participants were involved.…”
Section: Pre-service Teachers' Understanding Of Quadrilateralssupporting
confidence: 65%
See 3 more Smart Citations